Gastro Intestinal Disorders and Homoeopathy - A Retrospective Study (Advancements in Homeopathic Research, 2022)
Introduction: Gastro intestinal diseases are the  most common disorders seen worldwide. Microbiota  is a term used for eukaryotic and prokaryotic  microorganisms. In case of infected persons, it  can produce symptoms like diarrhea, vomiting,  nausea, flatulency, pain abdomen, inflammation of  intestine, etc. The most common presentations of  Gastro intestinal disorders are heart burn, nausea and  vomiting, dysphagia, indigestion, chronic recurrent  pain abdomen, flatulency, belching, loss of weight,  etc. Homoeopathy is a system where symptom  similiarity and individualization is considered in  remedy selection.The vulnerability and frequency  of disease will decrease when medicine prescribed  is based on individualization. This is a retrospective  study analyzing the previous case history to assess  the efficacy of homoeopathy in gastrointestinal  disorders. Materials and Methods: Case records of 261  patients diagnosed with gastrointestinal disorders  with symptoms like pain abdomen, nausea, vomiting,  heart burn, flatulence, diarrhea, bleeding per rectum,  dysuria, hesitancy in urine etc. who had visited OPD  of NHRIMH Kottayam Kerala from January 2022  to May 2022 (5 months) had been retrospectively  analyzed to find out the most common gastrointestinal  disorders and frequently indicated useful remedies in  managing the patient.  Results and Discussion It has been found that in our study maximum affection  is in the age group of 51-60 and least in the age group  of 91-100. Females were most affected than males.  45 new patients and 216 old patients had visited. The  most common gastro intestinal disorders for which patients visited were Cholelithiasis, Gastritis and  GERD.Most frequently indicated medicines were Nux  vomica (20.69%), Sulphur (16.48%), Bryonia  (9.96%), Argentum nitricum (9.58%) and  Lycopodium (9.20%).The study showed drastic improvement in all the  patients which proves that homoeopathy is highly  effectivein gastrointestinal disorders.  Conclusion From the above retrospective study, it is clear that  when the homoeopathic principles were followed  properly in treating a patient we can arrive at a  permanent cure in all patients without any side  effects.
Keywords: Gastro intestinal diseases; Microbiota; Homoeopathy